The predictive role of right ventricular late gadolinium enhancement in patients with tetralogy of Fallot undergoing pulmonary valve replacement - Caterina Beatrice Monti; Moreno Zanardo; Davide Capra; Giulia Lastella; Gianluca Guarnieri; Emilia Giambersio; Giulia Pasqualin; Francesco Sardanelli; Francesco Secchi (European Radiology Experimental, 2023)
Abstract Background Our purpose was to evaluate the correlations between right ventricular (RV) late gadolinium enhancement (LGE) at cardiac magnetic resonance (CMR) in patients with tetralogy of Fallot (ToF) scheduled for pulmonary valve replacement (PVR) and post-PVR functional data. Methods We retrospectively reviewed ToF patients scheduled for PVR who underwent two CMR examinations at our institution, one before the procedure (CMR-0), including contrast-enhanced sequences, and one after the procedure (CMR-1). Functional left and RV data were obtained by segmenting short-axis stacks on both CMR examinations, and normalised variations were calculated by dividing differences between CMR-1 and CMR-0 by the intercurring time interval, whereas the RV scar burden was assessed on CMR-0 LGE sequences both semiquantitatively and quantitatively. Data were reported as median and interquartile range, differences were appraised with the Mann–Whitney U test, while correlations were assessed with Spearman’s ρ. Results Fifteen patients with a median age of 25 years (16–29), including 9 (60%) males, with a median time interval between CMR-0 and CMR-1 of 17 months (12–23), were retrospectively reviewed. The semiquantitative LGE score at CMR-0 was 7 (6–9), and LGE volume was 4.49 mL (3.70–5.78), covering 5.63% (4.92–7.00) of the RV. RV LGE score showed a moderate positive correlation with the normalised variation of RV stroke volume (ρ = 0.662, p = 0.007) and a borderline moderate positive correlation with the normalised variation of RV end-diastolic indexed volume (ρ = 0.513, p = 0.050). Conclusions The assessment of RV LGE before PVR may provide insights on post-PVR functional data, potentially facilitating a patient-tailored treatment pathway.